Including the irregularities in the light-weight floor/ceiling model - Chung, H; Fox, C (The Institute of the Noise Control Engineering of the USA, 2006)
Chung and Fox previously presented a mathematical/computational model giving good prediction of low-frequency vibration of light-weight timber based floor/ceiling structures (LTFS) made up of: upper plate, joist beams and ceiling. In that work the geometry of the structure was assumed known, and precise. Experimental data from mock-up LTFS validated that model. In this paper we present an augmentation of that model by including uncertainty in the placement and shape of the timber joists. We calculate the variability in vibration response in the low-frequency range by taking account of measurements of the bending and twisting of 301 timber beams. Although, the model was originally constructed for low-frequency vibration, its usefulness in the mid frequency range ( > 150Hz ) is discussed. Earlier results showed that the rigidity of the connection between the upper plate and joist beams plays an important role in predicting resonance frequencies and vibration levels. We further consider these connection conditions in the presence of uncertainty.